Preconditioning with ozone/oxygen mixture presented improved histopathological protection compared to hyperbaric oxygen treatment in a rat global cerebral ischemia model - Oter, S.; Oztas, E.; Seyrek, M.; Uysal, B.; Duz, B.; Kaplan, M.; Kahraman, S. (Nature Publishing Group, 2009)
[Abstract Not Available]
24th International Symposium on Cerebral Blood Flow and Metabolism/9th International Conference on Quantification of Brain Function with PET -- JUN 29-JUL 03, 2009 -- Chicago, IL
Keywords: Ozone Therapy